Penggunaan Insektisida Rumah Tangga dan Kerentanan Aedes sp terhadap Permetrin di Kelurahan Sorosutan Kota Yogyakarta - Arlina Azka; Fardhiasih Dwi Astuti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2021)
Abstract. The use of household insecticides is an alternative solution to prevent mosquito bites.Most of the household insecticides sold in Indonesia have pyrethroid active ingredients, permethrin,which is available in the aerosol formulation. Inappropriate use of household insecticides can reducemosquito susceptibility. The objectives of this study are to describe the use of household insecticidesand susceptibility of Aedes sp. against permethrin in Sorosutan Yogyakarta. This study used a crosssectionalsurvey design. This study was conducted in December 2018–April 2019 in 354 householdsin Sorosutan which were randomly selected based on proportional sampling. Interviews about thehousehold insecticides were conducted with the owner or resident of the house. The susceptibilitytests used impregnated paper with permethrin 0.75%. The survey results showed that 25.14% ofthe houses use household insecticides. The insecticide used were aerosol, electric mosquito repellents,and mosquito coils containing active ingredients of the pyrethroid group, namely dimefl uthrin,transfl uthrin, prallethrin, cypermethrin, and metofl uthrin. The susceptibility test results showed adecrease in mosquito susceptibility where the population of Aedes sp. in Sorosutan has been resistantagainst permethrin. The continuous use of insecticides with pyrethroid active ingredients can developmosquito resistance against permethrin because all pyrethroids have the same mode of action. Thisstudy concludes that only a small proportion (25,14%) of the households used insecticides with theactive ingredients used mainly in the pyrethroid group (dimefl uthrin, transfl uthrin, prallethrin,cypermethrin, and metofl uthrin) and the population of Aedes sp. in Sorosutan has been resistant topermethrin.